If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -6 + -1t = 5 Reorder the terms: -6 + 6t + -1t = 5 Combine like terms: 6t + -1t = 5t -6 + 5t = 5 Solving -6 + 5t = 5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5t = 5 + 6 Combine like terms: -6 + 6 = 0 0 + 5t = 5 + 6 5t = 5 + 6 Combine like terms: 5 + 6 = 11 5t = 11 Divide each side by '5'. t = 2.2 Simplifying t = 2.2
| 3cotx+2tanx=5 | | 3(-9-4x)=21 | | -2.6x+7.48=-5 | | -2.6+7.48=-5 | | (X^2-7)/14x | | 8(2x+2)=64 | | 4/2-10 | | 4y-14=3y-7 | | -12.48x+7.48=-5 | | 12x-13=5x+15 | | .3090y=3 | | -12.48+7.48=-5 | | 4(4x+2)=2(1+6x)+14 | | 7x^2=-2x-6 | | 4x-4=-5x-103 | | (X-4)*8=72 | | 6-7x=-x-48 | | 5c-2=8 | | X-.25x=101.25 | | 6a+6=7 | | (1)=2+-0.5y | | 3m^2-42=8 | | 3/7x=13 | | (-2)=2+-0.5y | | -4x^2+13x-3=0 | | -7(3x-6)-4(2x+9)= | | 7/8g=8/10 | | 15x-12=-9x | | 7@/8g=8/10 | | 14/38=x/29 | | 3(2x-4)=8+2x+6 | | -0.75x+0.25=0.5x-0.75 |